2008
DOI: 10.1051/vetres:2007063
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical visualisation and spatial statistics for evaluation of the dispersion of epidemic highly pathogenic avian influenza subtype H5N1

Abstract: -The aim of this study was to evaluate a range of statistical and geostatistical methods for their usefulness in providing insights into how highly pathogenic avian influenza (HPAI) subtype H5N1 might spread through a national population of village poultry. The insights gained allow the generation of disease dispersion hypotheses. The case study data set consisted of 161 outbreaks of HPAI subtype H5N1 in village poultry reported in Romania between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Then the local indicator of spatial autocorrelation (LISA) statistic was estimated (Spatial Analyst, ArcGIS TM 9.3. ESRI Inc., Redland CA) to detect any clusters of model residuals (Anselin, 2005;Ward et al, 2008b), and LISA analysis identified significant (P<0.05) clusters of residuals in the east and southwest of Bhutan. However, no significant (P=0.068) spatial autocorrelation (I=0.042) was detected in the model standardized residuals when the spatial relationship between sub-districts were defined using the second order rook contiguity weight matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Then the local indicator of spatial autocorrelation (LISA) statistic was estimated (Spatial Analyst, ArcGIS TM 9.3. ESRI Inc., Redland CA) to detect any clusters of model residuals (Anselin, 2005;Ward et al, 2008b), and LISA analysis identified significant (P<0.05) clusters of residuals in the east and southwest of Bhutan. However, no significant (P=0.068) spatial autocorrelation (I=0.042) was detected in the model standardized residuals when the spatial relationship between sub-districts were defined using the second order rook contiguity weight matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analyses of the lineage relationship were executed on the virus strains isolated in eastern Asia , South Korea (Lee et al, 2008), Nigeria (Ducatez et al, 2006) and western Africa (Ducatez et al, 2007). Local level space-time cluster analyses of H5N1 outbreaks over short time periods have been carried out in China (Oyana et al, 2006), Vietnam (Pfeiffer et al, 2007) and Romania (Ward et al, 2008). The purpose of these studies was to identify spatio-temporal patterns of the spread of the disease and to ascertain possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…If H5N1 is spread by wild birds, either over long or over short distances, this might be deduced from spatial-temporal patterns of the disease outbreaks (Onozuka and Hagihara, 2008;Ward et al, 2008). Wild birds utilize large number of over-staging sites along the flyways to forage during the migration, and settle in breeding and wintering sites during the non-migration seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for the detection of spatial and spatiotemporal clusters described elsewhere (Carpenter 2001) have been commonly applied as a useful tool in other highly infectious disease epidemics, such as foot-and-mouth disease (FMD) or avian influenza (AI) (Perez et al 2004, Ward et al 2008.…”
Section: Introductionmentioning
confidence: 99%